PENUKAR KALOR CANGKANG DAN TABUNG EFEKTIF UNTUK MENDINGINKAN MINYAK PELUMAS MESIN DIESEL DENGAN PENYARINGAN SISTEM CABANG - Murni Murni (Diponegoro University, 2007)
Lubrication is important parameter in whole operation in diesel engine, bad lubrication will affect trouble inoperation lubrication have double function decrease friction and cooling. So lubrication has to be treatmentto increase quality by cooling method. Cooling method is done with bat exchanger of shell and tube type. .